Culturing cells for life: innovative approaches in macroscopic and microfluidic cultures, with an emphasis on stem cells - Badilescu, Simona; Parimalam, Subhathirai Subramaniyan; Packirisamy, Muthukumaran (Frontiers in Nanotechnology, 2023)
In 2006, Whitesides, writing about microfluidics, said that microfluidics is in early adolescence and it is not yet clear how it will develop (1). Today, almost twenty years later, microfluidics became a fully developed, highly sophisticated, multidisciplinary field that had entirely honoured its early promise. Its strength stems from the knowledge and know-how, coming from multiple disciplines such as physics of fluids, engineering, and microfabrication in the beginning, followed, more recently, by cell biological research, in full bloom nowadays. In microfluidic devices, the environment of cells such as chemical and mechanical gradients can be reproduced, making biological studies even more compelling. The red thread of this review paper follows the new insights and discoveries in both traditional macroand microfluidic cell culture brought into the cell biology field, especially in the culture of stem cells, filled with promise in the field of regenerative medicine. Microfluidic devices provide an environment that is much closer to that of in vivo cell culture than the conventional culture platforms, where large amounts of cells are cultured and the environment of individual cells cannot be distinguished. The convenience of live cell imaging, portability, and the integration of sensors to precisely, control various parameters, has expanded cell biologists' arsenal In addition, microfluidic devices, integrated with different functionalities, that is, the automated cell culture systems, will be discussed as well.